Assessing a National Collaborative Program To Prevent Catheter-Associated Urinary Tract Infection in a Veterans Health Administration Nursing Home Cohort. (10th May 2018) - Krein, Sarah L.; Greene, M. Todd; King, Beth; Welsh, Deborah; Fowler, Karen E.; Trautner, Barbara W.; Ratz, David; Saint, Sanjay; Roselle, Gary; Clifton, Marla; Kralovic, Stephen M.; Martin, Tina; et al.
Abstract : OBJECTIVE: Collaborative programs have helped reduce catheter-associated urinary tract infection (CAUTI) rates in community-based nursing homes. We assessed whether collaborative participation produced similar benefits among Veterans Health Administration (VHA) nursing homes, which are part of an integrated system. SETTING: This study included 63 VHA nursing homes enrolled in the "AHRQ Safety Program for Long-Term Care, " which focused on practices to reduce CAUTI. METHODS: Changes in CAUTI rates, catheter utilization, and urine culture orders were assessed from June 2015 through May 2016. Multilevel mixed-effects negative binomial regression was used to derive incidence rate ratios (IRRs) representing changes over the 12-month program period. RESULTS: There was no significant change in CAUTI among VHA sites, with a CAUTI rate of 2.26 per 1, 000 catheter days at month 1 and a rate of 3.19 at month 12 (incidence rate ratio [IRR], 0.99; 95% confidence interval [CI], 0.67–1.44). Results were similar for catheter utilization rates, which were 11.02% at month 1 and 11.30% at month 12 (IRR, 1.02; 95% CI, 0.95–1.09). The numbers of urine cultures per 1, 000 residents were 5.27 in month 1 and 5.31 in month 12 (IRR, 0.93; 95% CI, 0.82–1.05). CONCLUSIONS: No changes in CAUTI rates, catheter use, or urine culture orders were found during the program period. One potential reason was the relatively low baseline CAUTI rate, as compared with a cohort of community-based nursing homes. This low baseline rate is likely related to the VHA's prior CAUTI prevention efforts. While broad-scale collaborative approaches may be effective in some settings, targeting higher-prevalence safety issues may be warranted at sites already engaged in extensive infection prevention efforts. Infect Control Hosp Epidemiol 2018;820–825